Misperception of weight status in the pacific: preliminary findings in rural and urban 11- to 16-year-olds of New Caledonia - Stéphane Frayon; Sophie Cherrier; Yolande Cavaloc; Guillaume Wattelez; Amandine Touitou; Paul Zongo; Kalina Yacef; Corinne Caillaud; Yannick Lerrant; Olivier Galy (BMC, 2017)
Abstract Background Adolescent obesity is prevalent in Pacific region ethnic groups (European, Melanesian and Polynesian) living in both urban and rural areas. Although body perception is an important factor of weight gain or loss, little is known about the body self-perceptions of Pacific region adolescents. This study therefore evaluated adolescent perceptions of body weight according to ethnicity (European, Melanesian or Polynesian), socioeconomic status (low, intermediate or high) and living area (rural or urban) in New Caledonia. Methods Sociodemographic and anthropomorphic data from 737 adolescents (351 boys and 386 girls) with ages ranging from 11 to 16 years were collected and analysed. The International Obesity Task Force (IOTF) standards were used to define weight status as normal-weight, underweight or overweight/obese. Weight perception was assessed from detailed questionnaires, with adolescents rating their own weight with the following descriptors: 'about the right weight', 'too heavy', or 'too light'. Results Results showed that only 8.5% of normal-weight adolescents (7% boys and 10% girls) identifying themselves as 'too heavy'. Normal-weight Melanesian adolescents were less likely than their European counterparts to assess themselves as too heavy (OR = 0.357). However, half the overweight/obese adolescents underestimated their weight status (53% boys and 48% girls). Weight misperception was associated with ethnicity, socioeconomic status and living area, with gender-specific differences. Conclusions The results of this study suggest that these sociodemographic factors should be taken into account when designing public health policies and health education school programmes in New Caledonia and, more broadly, the Pacific region.